Micro/Nano Materials for Clean Energy and Environment - Tan, Zhongchao (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Tsinghua University-University of Waterloo Joint Research Center for Micro/Nano Energy & Environment Technology (JCMEET) is a platform. It was established on Nov.11, 2017. The Chairperson of University Council of Tsinghua University, Dr. Xu Chen, and the President of the University of Waterloo, Dr. Feridun Hamdullahpur, attended the opening ceremony and unveiled the nameplate for the joint research center on 29th of March, 2018. The research center serves as a platform for researchers at both universities to conduct joint research in the targeted areas, and to meet regularly for information exchange, talent exchange, and knowledge mobilization, especially in the fields of micro/nano, energy, and environmental technologies. The center focuses on three main interests: micro/nano energy technology, micro/nano pollution control technology, and relevant fundamental research. In order to celebrate the first anniversary of the Joint Research Center, we were invited to serve as the Guest Editors of this Special Issue of Materials focusing on the topic of micro/nano-materials for clean energy and environment. It collects research papers from a broad range of topics related to micro/nanostructured materials aimed at future energy resources, low emission energy conversion, energy storage, energy efficiency improvement, air emission control, air monitoring, air cleaning, and many other related applications. This Special Issue provides an opportunity and example for the international community to discuss how to actively address the energy and environment issues that we are facing.